PENGARUH MOTIVASI PENGETAHUAN PERPAJAKAN, MOTIVASI KARIR, MOTIVASI KUALITAS, MOTIVASI SOSIAL, DAN MOTIVASI EKONOMI TERHADAP MINAT MAHASISWA MENGIKUTI PROGRAM BREVET PAJAK - Apri Ani Rahayu; Teguh Erawati; Anita Primastiwi (Jurnal Riset Perpajakan: Amnesty, 2021)
The tax brevet is an effort to pursue the world of taxation as the first step for students and enthusiasts in a career in taxation. The lack of knowledge about the importance of this tax brevet makes students' interest in participating in the tax brevet low. This makes researchers interested in researching the influence of motivation that can affect student interest in participating in tax brevet. This background is the basis for conducting research with the title "The Influence of Tax Knowledge Motivation, Career Motivation, Quality Motivation, Social Motivation, and Economic Motivation on Student Interest in Participating in the Tax Brevet Program". The population used in this study were accounting students from the 2016 2017 and 2018 classes. The sampling technique used was the purpose sampling method. The data used is primary data obtained from the distribution of questionnaires as many as 86 people. The analysis technique used is multiple linear regression test. The results of this study concluded that the motivation for tax knowledge, quality motivation, and economic motivation had a positive effect on student interest in participating in tax brevet; and career motivation and social motivation have a negative effect on student interest in participating in tax brevet.